Leverrier-Takeno Coefficients for the Characteristic Polynomial of a Matrix - Guerrero-Moreno, I.; López-Bonilla, J.; Rivera-Rebolledo, J. (Journal of the Institute of Engineering, 2011)
It is shown for any Anxn an elementary method, in terms of the spur of Ak, k = 1,...,n , to determine the coefficients of its characteristic polynomial. Keywords: Polynomial DOI: http://dx.doi.org/10.3126/jie.v8i1-2.5118 Journal of the Institute of Engineering Vol. 8, No. 1&2, 2010/2011 Page: 255-258 Uploaded Date: 20 July, 2011